An RNA G‐Quadruplex Structure within the ADAR 5′UTR Interacts with DHX36 Helicase to Regulate Translation. (23rd November 2022) - Lyu, Kaixin; Chen, Shuo‐Bin; Chow, Eugene Yui‐Ching; Zhao, Haizhou; Yuan, Jia‐Hao; Cai, Meng; Shi, Jiahai; Chan, Ting‐Fung; Tan, Jia‐Heng; Kwok, Chun Kit
Abstract: RNA G‐quadruplex (rG4) structures in the 5′ untranslated region (5′UTR) play crucial roles in fundamental cellular processes. ADAR is an important enzyme that binds to double‐strand RNA and accounts for the conversion of Adenosine to Inosine in RNA editing. However, so far there is no report on the formation and regulatory role of rG4 on ADAR expression. Here, we identify and characterize a thermostable rG4 structure within the 5′UTR of the ADAR1 mRNA and demonstrate its formation and inhibitory role on translation in reporter gene and native gene constructs. We reveal rG4‐specific helicase DHX36 interacts with this rG4 in vitro and in cells under knockdown and knockout conditions by GTFH (G‐quadruplex‐triggered fluorogenic hybridization) probes and modulates translation in an rG4‐dependent manner. Our results further substantiate the rG4 structure‐DHX36 protein interaction in cells and highlight rG4 to be a key player in controlling ADAR1 translation. Abstract : An RNA G‐quadruplex (rG4) structure was identified in the 5′UTR of the ADAR1 mRNA using multi‐disciplinary assays in vitro and cells. The binding and resolving effect of rG4‐specific helicase DHX36 on this rG4 was monitored using G‐quadruplex‐triggered fluorogenic hybridization (GTFH) probe. Functionally, ADAR1 5′UTR rG4 inhibits reporter gene and native transcript translation with DHX36 modulating its formation in cells.